Liquid milk: Savings, insurance and side-selling in cooperatives - Geng, Xin; Janssens, Wendy; Kramer, Berber (Elsevier, 2023)
Limited access to reliable financial instruments makes it difficult for rural households to manage daily cash flows. Selling goods through cooperatives can improve savings, but cooperative income is not easily accessible when facing an emergency. Cash-constrained households may therefore side-sell in local markets that pay on the spot, while insurance could reduce the need to side-sell. We test these hypotheses using panel data for farmers from two Kenyan dairy cooperatives. Both cooperatives pay only once a month, with local market vendors paying a lower price but upon delivery. We find that farmers sell less milk to the cooperatives when facing uninsured health emergencies or when cash on hand is low. Health insurance reduces side-selling. These findings highlight that selling, saving and risk-coping decisions are intertwined, with side-selling providing a strategy to manage temporary cash constraints. This suggests that linking agricultural and insurance contracts can enhance cooperatives’ financial sustainability.